2018
DOI: 10.1002/cssc.201801756
|View full text |Cite
|
Sign up to set email alerts
|

Interface‐Engineered Li7La3Zr2O12‐Based Garnet Solid Electrolytes with Suppressed Li‐Dendrite Formation and Enhanced Electrochemical Performance

Abstract: High grain-boundary resistance, Li-dendrite formation, and electrode/Li interfacial resistance are three major issues facing garnet-based solid electrolytes. Herein, interfacial architecture engineering by incorporating 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl) imide (BMP-TFSI) ionic liquid into a garnet oxide is proposed. The "soft" continuous BMP-TFSI coating with no added Li salt generates a conducting network facilitating Li transport and thus changes the ion conduction mode from point con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 72 publications
0
40
0
Order By: Relevance
“…Zhang et al proposed an interfacial architecture engineered by incorporating an ionic liquid into the garnet-based structure to avoid dendrite formation (Figure 13E). 111 In their design, the voids were inside the SE with poor contact with Li, which were the main reason for dendrite growth. They later utilized soft and continuous ionic liquid to fill the voids and connect the grain boundaries.…”
Section: Llmentioning
confidence: 99%
“…Zhang et al proposed an interfacial architecture engineered by incorporating an ionic liquid into the garnet-based structure to avoid dendrite formation (Figure 13E). 111 In their design, the voids were inside the SE with poor contact with Li, which were the main reason for dendrite growth. They later utilized soft and continuous ionic liquid to fill the voids and connect the grain boundaries.…”
Section: Llmentioning
confidence: 99%
“…That will transform the Li + conduction mode from point contacts to face‐contacts, leading to uniform ion transportation and high Young modulus for a direct blocking of lithium dendrite. Various interlayers were proposed to inhibit the lithium dendrites, including the soft butylmethylpyrrolidinium‐bis(trifluoromethanesulfonyl)imide (BMP‐TFSI) coating, [ 112 ] flexible PEO‐based capsulation, [ 113 ] chemically stable LiPON layer, [ 108 ] highly conductive Al 2 O 3 or MoS 2 layer, [ 103,104 ] high‐modulus Li 3 PO 4 addition. [ 114 ] Further, it was found that the chemically stable Li/LLZO interfaces may result in more lithium dendrite than that at unstable Li/LATP interfaces, which could be attributed to the terminated dendrite propagation by the generated interphase at the Li/LATP interface.…”
Section: Interfaces In All‐solid‐state Lithium Batteriesmentioning
confidence: 99%
“…On the other hands, conductivity difference in the grain, grain boundary or the interface (SEI and electrolyte) will lead to the preferential deposition of dendrite. [ 168 ]…”
Section: Lithium Anodesmentioning
confidence: 99%